2023
DOI: 10.3389/fphar.2023.1330877
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness and safety of PD-1/PD-L1 inhibitors in advanced or recurrent endometrial cancer: a systematic review and meta-analysis

Songfei Han,
Cuishan Guo,
Zixuan Song
et al.

Abstract: Background: Studies in recent years have shown that PD-1/PD-L1 inhibitors may have better effectiveness in patients with advanced or recurrent endometrial cancer. The effectiveness of PD-1/PD-L1 inhibitors is thought to be related to mismatch repair-deficient (dMMR) and mismatch repair-proficient (pMMR) classification in advanced or recurrent endometrial cancer. This study aims to evaluate the effectiveness of PD-1/PD-L1 inhibitors in patients classified as dMMR and pMMR.Methods: Medical databases were searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 56 publications
0
2
0
Order By: Relevance
“…The incidence of abnormal (ectopic) cells in endometriosis-affected endometrium is significantly elevated compared to normal endometrial tissue. While prior studies have not indicated a heightened risk of malignant transformation in endometriosis patients, they have identified an increased incidence of ovarian cancer, endometrial cancer, non-Hodgkin’s lymphoma, colorectal cancer, thyroid cancer, and melanoma within this population [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The incidence of abnormal (ectopic) cells in endometriosis-affected endometrium is significantly elevated compared to normal endometrial tissue. While prior studies have not indicated a heightened risk of malignant transformation in endometriosis patients, they have identified an increased incidence of ovarian cancer, endometrial cancer, non-Hodgkin’s lymphoma, colorectal cancer, thyroid cancer, and melanoma within this population [ 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Elucidating the role of the PD-1/PD-L1 pathway in endometriosis opens new avenues for targeted therapeutic interventions. Inhibitors of PD-1 and PD-L1, which are currently utilized in oncology, hold the potential for modulating the immune response in endometriosis [ 31 , 32 ]. Therapeutic strategies aimed at downregulating PD-L1 expression or blocking the PD-1/PD-L1 interaction could enhance the immune system’s efficacy against ectopic endometrial tissue, thereby introducing novel treatment options for endometriosis management.…”
Section: Discussionmentioning
confidence: 99%